Hormone use for menopausal symptoms and risk of breast cancer. A Danish cohort study - Ewertz, M (Nature Publishing Group, 2005)
Numerous studies and meta-analyses have shown that hormone replacement therapy (HRT) for menopausal symptoms increases the risk of developing breast cancer, estimated to be 2.3% for each year of use. The influence of different oestrogen–progestin regimens has still not been fully evaluated. Using longitudinal data from the population-based prescription database of the county of North Jutland, Denmark, and the Danish Cancer Registry, we examined the risk of developing breast cancer in relation to HRT in a cohort of 78 380 women aged 40–67 years from 1989 to 2002. A total of 1462 cases of breast cancer were identified during a mean follow-up of 10 years. Use of HRT did not increase the risk of breast cancer in women aged 40–49 years. Restricting the cohort to 48 812 women aged 50 years or more at entry, of whom 15 631 were HRT users, we found an increased risk associated with current use of HRT (relative risk 1.61, 95% confidence interval 1.38–1.88). The risk increased with increasing duration of use and decreased with time since last HRT prescription, reaching unity after 5 years. No material risk difference was observed among the various HRT-regimens. This population-based cohort study provides further confirmation that HRT increases the risk of developing breast cancer in women aged 50 years or more.